Effect of the 21-aminosteroid tirilazad mesylate on leukocyte adhesion and macromolecular leakage during endotoxemia - Schmidt, Heinfried; Schmidt, Werner; Müller, Thomas; Böhrer, Hubert; Bach, Alfons; Gebhard, Martha-Maria; Martin, Eike (Surgery, 1997)
Background. Interstitial accumulation of leukocytes has been related to the development of multiple organ failure after sepsis. Oxygen radicals are involved in the process of leukocyte adherence to the microvascular wall. This study investigates the effects of the oxygen radical scavenger tirilazad mesylate on leukocyte-endothelial interactions, macromolecular leakage, and microhemodynamics in mesenteric venules during endotoxemia. Methods. Male Wistar rats were randomly allocated to receive tirilazad mesylate (group A, n = 10), its vehicle (group B, n = 10), or saline 0.9% (group C, n = 10) before a 120-minute infusion of endotoxin (2 mg/kg/hr). Furthermore, a control group without receiving endotoxin (group D, n = 10) was investigated. Leukocyte adherence, emigration of leukocytes, and macromolecular leakage were determined in postcapillary venules of the mesentery by using intravital videomicroscopy. Results. During the administration of endotoxin the number of adherent leukocytes per square millimeter of vessel surface progressively increased in group B (baseline, 431 ± 35 cells/mm2; 120 minutes, 1121 ± 71 cells/mm2) and group C (baseline, 398 ± 44 cells/mm2; 120 minutes, 1290 ± 116 cells/mm2). In group A no increase in leukocyte adherence was observed after 120 minutes (baseline, 415 ± 81 cells/mm2; 120 minutes, 638 ± 87 cells/mm2). In control animals the leukocyte adherence remained unchanged (baseline, 347 ± 41 cells/mm2; 120 minutes, 507 ± 75 cells/mm2). After 120 minutes, tirilazad mesylate prevented the increase in leukocyte emigration observed in groups B and C. Increased macromolecular leakage during endotoxemia (groups B and C) was not influenced by pretreatment with tirilazad. Tirilazad did not affect the decrease in red cell velocity, volumetric blood flow, and venular shear rate observed during endotoxemia. Conclusions. This study demonstrates inhibitory effects of tirilazad on endotoxin-induced leukocyte adherence and emigration, suggesting a potential therapeutic role for this substance in the prevention of sepsis-induced multiple organ failure.